WORLD EXPERIENCES OF ASSESSING THE EFFECTIVENESS OF STRATEGIC MANAGEMENT OF BUSINESS ENTITIES - M.G. Shakirova (Scholar Express Journals, 2024)
Analysis of the category of efficiency, its determining factors, the content and results of management work allows us to conclude that groups of indicators correspond to the content and forms of the manifestation of efficiency, which can serve as efficiency criteria. about the purpose of the organization and its working conditions. Each option of the control system corresponds to a certain value of the efficiency criterion, and the task of control is to find the control option for which the corresponding criterion takes the optimal value.
Keywords: optimal; certain; efficiency; determining